IMPACT OF ENVIRONMENTAL TOBACCO SMOKE EXPOSURE ON ADULTS WITH ASTHMA EXACERBATION - SUTARYONO; HARTONO; PROBANDARI, ARI; SETYONO, PRABANG (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Environment tobacco smoke (ETS) exposure in the household is dangerous to infants and children. Nicotine residue inhaled in the respiratory tract metabolized into cotinine which has the possibility of causing inflammation which can result in asthma exacerbation. The impact created by the exposure of ETS on children suffering from asthma is the sole objective of this research work. Methods: A cohort study was carried out among 114 asthma patients aged 12–18 years old at three hospitals from January 2016 to March 2017. Data were obtained using self-reported questionnaires and cotinine urine test. The data analysis was carried with the use of Cox proportional hazard model with 95% confidence interval (CI). Results: The result of the research showed that 57% of the patients got the trigger (event). The respondents consisted of 61.5% of female, average age of 15 years, 50.8% of upper secondary education, 55.4% of body mass index (BMI) normal, and 63.1% low economic status persons. Median survival for the ETS-exposed group was in a 9th week, while the median survival for the ETS non-exposed group was >12 weeks. Multivariate exposure of ETS with asthma exacerbation was hazard ratio (HR), 2.17; 95% CI, 1.23–3.83, p=0.008 and gender HR, 1.72; 95% CI, 1.04–2.85, p=0.035. Conclusion: ETS exposure in the household increases the risk of asthma exacerbation. Controlling the environment and education of children to avoid ETS exposure should be intensified.